The Effect of e-CRM, e-Marketing and e-Loyalty and Company Performance of Defense Industries - Harliyanto, Deddy; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this research is to analyze the relationship of e-Marketing (EM) on Company Performance, e-CRM (EC) on Company Performance ,e-Marketing (EM) on e-Loyalty , e-CRM (EC) have a positive effect on e-Loyalty (EL), e-Loyalty (EL) on Company , e-CRM (EC) on Company Performance (CP) through e-Loyalty (EL) and e-Marketing (EM) on Company Performance (CP) through e-Loyalty (EL). This research is a quantitative research with a questionnaire approach. Data processing tools use the SmartPLS 3.3.3 software. The primary data collection method was by distributing online questionnaires through online surveys to 110 staff of defense industries. The questionnaire consisted of two parts. The first part contains questions to collect respondents' demographic information. The second part is the main component of the questionnaire that is statements related to the research variables. Based on regression test results shows the result e-Marketing has significant effect on Company Performance, e-CRM has significant effect on Company Performance, e-Marketing has not significant effect on e-Loyalty, e-CRM has not significant effect on e-Loyalty, e-Loyalty has not significant effect on Company Performance, e-CRM has not significant effect on business sustainability through e-Loyalty. e-Marketing has not significant effect on Company Performance through e-Loyalty.